Is Preoperative Diagnosis Possible? A Clinical and Radiological Review of Lymphoepithelial Cysts of the Pancreas - Osiro, Stephen; Rodriguez, Jonier R; Tiwari, Kevin J; Rodriguez, Iliana I; Mathenge, Njambi; Tubbs, Robert Shane; Loukas, Marios (JOP. Journal of the Pancreas, 2013)
Lymphoepithelial cysts of the pancreas are rare lesions found mainly in middle-aged men. They are usually benign and have no clear natural history except one study linking their occurrence with HIV infection. Nevertheless, they often cause enormous psychological stress to patients as they tend to mimic pancreatic neoplasms which are known to carry poor prognosis. The authors have therefore assessed the published literature from PubMed in order to determine whether lymphoepithelial cysts can be diagnosed preoperatively using novel imaging techniques. Based on our findings, it is evident that three-dimensional computed tomography scans, in-phase and out-of phase magnetic resonance imaging studies, and endosonography have enabled better characterization of pancreatic lymphoepithelial cysts than a decade ago. Endoscopic ultrasound-guided fine needle aspiration has also added considerably to the promise of preoperative diagnosis. Thus, the authors can affirm that despite surgical excision of the cyst with pathological examination being the gold standard for diagnosis, it is possible that a combination of the modern imaging techniques and/or minimally-invasive approach can enable patients avoid unnecessary surgery in the future. Image: Proposed algorithm for diagnosis and management of lymphoepithelial cysts.